Efficacy of statins in familial hypercholesterolaemia: a long term cohort study. (11th November 2008) - Versmissen, Jorie; Oosterveer, Daniëlla M; Yazdanpanah, Mojgan; Defesche, Joep C; Basart, Dick C G; Liem, Anho H; Heeringa, Jan; Witteman, Jacqueline C; Lansberg, Peter J; Kastelein, John J P; Sijbrands, Eric J G
Abstract : Objective To determine the efficacy of statin treatment on risk of coronary heart disease in patients with familial hypercholesterolaemia. Design Cohort study with a mean follow-up of 8.5 years. Setting 27 outpatient lipid clinics. Subjects 2146 patients with familial hypercholesterolaemia without prevalent coronary heart disease before 1 January 1990. Main outcome measures Risk of coronary heart disease in treated and "untreated" (delay in starting statin treatment) patients compared with a Cox regression model in which statin use was a time dependent variable. Results In January 1990, 413 (21%) of the patients had started statin treatment, and during follow-up another 1294 patients (66%) started after a mean delay of 4.3 years. Most patients received simvastatin (n=1167, 33 mg daily) or atorvastatin (n=211, 49 mg daily). We observed an overall risk reduction of 76% (hazard ratio 0.24 (95% confidence interval 0.18 to 0.30), P<0.001). In fact, the risk of myocardial infarction in these statin treated patients was not significantly greater than that in an age-matched sample from the general population (hazard ration 1.44 (0.80 to 2.60), P=0.23). Conclusion Lower statin doses than those currently advised reduced the risk of coronary heart disease to a greater extent than anticipated in patients with familial hypercholesterolaemia. With statin treatment, such patients no longer have a risk of myocardial infarction significantly different from that of the general population.